PENGEMBANGAN MODUL DIGITAL MENGGUNAKAN KODULAR PADA MATERI GARIS DAN SUDUT KELAS VII SMP NEGERI 30 PADANG - Anggraini, Ayu; Melisa; Delyana, Hafizah (Jurnal Riset Pembelajaran Matematika, 2024)
This research aims to produce a digital module using a coder on lines and angles that is valid and practical for class VII students at SMP Negeri 30 Padang. This type of research is R&D (Research and Development) development research with a 4-D development model. The results of the digital module validation test using codular were 81.73% with a very valid category. The practicality results for digital modules using codular are 94.95% in the very practical category. Based on the research results, it can be concluded that the digital module using codular material on lines and angles in class VII SMP Negeri 30 Padang is suitable for use and is in the valid and practical category.